Effects of Supraorbital Foramen Variations on the Treatment Efficacy of Radiofrequency Therapy for V1 Trigeminal Neuralgia: A Retrospective Study. (26th February 2020) - Xie, Keyue; Liu, Songlei; Huang, Bing; Yao, Ming
Abstract : Background . Primary V1 trigeminal neuralgia is a common refractory neuralgia in clinical practice, lacking effective treatments. Radiofrequency therapy has certain treatment efficacy, but its long-term efficacy remained poor and the disease might relapse. Objective . To compare the effects of different types of supraorbital foramen variations on the treatment efficacy of radiofrequency therapy for V1 trigeminal neuralgia. Methods . Data of 54 patients with V1 trigeminal neuralgia who underwent treatment in the First Hospital of Jiaxing, Zhejiang, were retrospectively analyzed. All these patients received CT-guided radiofrequency thermocoagulation of supraorbital nerve. According to the CT images, the supraorbital foramen of the patients was categorized as holes (hole group) or notches (notch group). The patient characteristics, including Numerical Rating Scale (NRS) score and effective treatment rates before and 1 d, 0.5 y, 1 y, and 2 y after operation, and numbness degree at day 1 and 2 y after the operation were compared. The short- and long-term complications during postoperative follow-up period were also recorded. Results . Among the 54 patients, 25 patients were grouped into the hole group and 29 into the notch group. The NRS scores before and at 1 d, 0.5 y, 1 y, and 2 y after operation showed no significant differences between the two groups. However, the NRS scores at the remaining time points after operation were significantly decreased when compared with scores before operation (P < 0.05 ). The numbness and numbness degree after operation showed no significant differences between the two groups. The numbness degree at 2 y after operation was significantly lower than 1 d after operation (P < 0.05 ). The effective rate at 1 d, 0.5 y, and 1 y after operation showed no significant differences between the hole and notch groups. However, the effective rate at 2 y after operation was significantly lower in the notch group than hole group (P < 0.05 ). No severe short- or long-term complications were found in either group. Conclusion . The short- and long-term effective rates of radiofrequency therapy during V1 trigeminal neuralgia treatment are relatively high in patients with different types of supraorbital foramen variations. However, the effective rate is even higher in patients with hole-type supraorbital foramen. No other severe complications, except numbness, were found, and the acceptability rate remained high in patients.